The Management of Diabetic Foot Ulcers Using the Wound Treatment Techniques of Modern Dressing: A Systematic Review - Mohammad Roni Alfaqih; Gabriel Wanda Sinawang; Rohmatul Faizah; Andrik Hermanto (Jurnal Ners, 2019)
Background: One of the complications caused by diabetes mellitus is the problem of diabetic foot ulcers (DFU). The management of the DFU problem can be carried out through the wound care focused on the foot using modern dressings. This research was to determine the effectiveness of modern dressings on the healing process of diabetic foot ulcers.Methods: The methods used in arranging this systematic review were (1) the identification of interventions in the literature, (2) the identification of relevant literature based on the topic and title, (3) obtaining the literature in full-text form and (4) the analysis of the results from the various interventions in the literature.Result: The literature search was carried out in several databases such as Scopus, Google Scholar and Pubmed. The samples in this article were research about the effect of modern dressings in the treatment of diabetic foot ulcers. A total of 22 evidence bases found 10 studies using the pre-experimental method, 3 RCTs, 2 quasi-experiments, 2 articles / systematic reviews, 2 perspective studies, 1 medical report, 1 case study and 1 vitro and vivo study.Conclusion: Based on the review, it explains that the research on modern dressings using nanocrystalline silver ion and curcumin can improves wound recovery by increasing the transformation rate of the ß1 growth factor, which is a protein involved in cell growth and proliferation.